Characterisation of adiponectin and its receptors in the bovine mammary gland and in milk. Issue 3 (March 2015) - Lecchi, Cristina; Giudice, Chiara; Uggè, Martina; Scarafoni, Alessio; Baldi, Antonella; Sartorelli, Paola
Highlights We studied the adiponectin system in the bovine mammary gland. The mRNA of AdipoQ and AdipoQ receptors was found in all analysed districts. Several adiponectin isoforms have been identified in bovine blood and milk. AdipoQ stained epithelial cells lining the secretory alveoli. AdipoQ was identified in small peripheral nerves.